Knowledge and perception of market women about the roles of physiotherapists in health promotion in Ghana: A qualitative phenomenological study - Opoku Kwadwo Konadu; Brenyah Joseph Kwasi; Isaac Mensah Bonsu (Heliyon, 2025)
Introduction: Promoting health is key to preventing major diseases, and physiotherapists play a vital role. However, market women often lack knowledge and awareness of their contributions to health promotion. Objective: The study seeks to explore the knowledge and perceptions of market women in Ghana regarding the roles of physiotherapists in health promotion. Methods: A qualitative research approach was employed to explore market women's perceptions of the role of physiotherapists in health promotion in Ghana. Using a convenient sampling method, in-depth interviews were conducted with 21 women from Kumasi Central Market (KCM) between August and October 2024. All interviews were audio-recorded and analyzed using Colaizzi's thematic analysis framework. Results: Market women's perceptions of physiotherapists' contributions to health promotion were characterized by three main themes: (i) awareness and understanding of physiotherapists in health promotion (ii) preferred communication channels for health promotion, and (iii) barriers to participation in health promotion programs. Market women's awareness of physiotherapy in Ghana tends to be limited, often perceiving physiotherapy as primarily for rehabilitation after injuries rather than a broader health promotion tool. This lack of understanding can prevent market women from recognizing physiotherapy's preventive and health-enhancing aspects, limiting their engagement in physiotherapist-driven initiatives. Conclusion: The findings indicate that market women are unaware of the role physiotherapists play in health promotion. Improving awareness, overcoming time and social barriers, and adapting communication strategies to local contexts are key to enhancing physiotherapy-driven health promotion among market women in Ghana.